Demographic, hematologic, and endoscopic differences between predominant corporeal and antral atrophic gastritis: A STROBE-Compliant study. Issue 49 (10th December 2021) - Chibulcutean, Oana; Gabor, Manuela Rozalia; Frandes, Sergiu-Ioan; Mocan, Simona; Dumitrascu, Dinu Iuliu; Negovan, Anca
Abstract : Abstract: The study aimed to assess demographic, clinical, and endoscopic parameters in patients with predominant corporeal atrophic gastritis (CAG) and enterochromaffin-like cell hyperplasia suggestive for autoimmune etiology in comparison with patients presenting Helicobacter pylori atrophic gastritis limited to the gastric antrum (AAG). Demographical, clinical, and pathological data of consecutive patients who underwent an upper digestive endoscopy for bleeding screening risk, symptoms, or anemia in a single endoscopy unit were retrieved. The final study group included 63 patients with CAG and enterochromaffin-like cell hyperplasia on histology and a control group of 142 patients with AAG. Female patients were predominant in the group with CAG versus AAG (69.8% vs 46.4%, P = .002). Microcytic anemia ( P < .001), but not macrocytic anemia ( P = .14) was associated with CAG, the mean corpuscular volume of erythrocyte (MCV) (82.5 vs 86.5 fl, P = .01), the mean value of serum iron (11.8 vs 14.3 μmol/L, P = .02), and hemoglobin level (11.0 vs 12.7 g/dL P < .01) being significantly lower in patients with CAG versus AAG. Upper digestive endoscopies with no visible mucosal lesions ( P = .01) were also more frequent in the patients with CAG, but there were not differences regarding digestive symptoms between groups. The linear regression models revealed that the low hemoglobin ( P < .001) and low MCV ( P = .03) are the independent variables that can predict CAG on histology, but not the serum iron level ( P = .77) Consecutive patients investigated on endoscopy with CAG in comparison with those having AAG are more frequent female, they have microcytic anemia, and no mucosal lesions on endoscopy. The decreased hemoglobin level and low MCV, rather than the serum iron level are predictors for CAG versus AAG on histology in endoscopic population.